Effect of Biologics on the Need for Procedural Interventions, Systemic Medications, and Healthcare Utilization in Patients with Hidradenitis Suppurativa: Real-World Data from the UNITE Registry - Marília Oliveira; Kassim Rahawi; Yinghui Duan; Michael Lane; Ahmad Z. Amin; Christopher J. Sayed (Adis, Springer Healthcare, 2023)
Abstract Introduction Management of hidradenitis suppurativa (HS) often requires a combined medical/procedural approach. Biologics are frequently reserved for severe cases after irreversible tissue damage has occurred. We evaluated the association between consistent biologic use and the need for procedural interventions, systemic medications, and healthcare utilization. Methods UNITE, a 4-year, global, prospective, observational, HS disease registry, documented the natural history, diagnostic/treatment patterns, and clinical outcomes of HS. Patients aged 12 years or more, with active HS were enrolled between October 2013 and December 2015 and evaluated every 6 months for 48 months at 73 sites across 12 countries (data cutoff December 2019). Proportions of patients requiring different HS procedures, systemic medications, and healthcare utilization were assessed during the 6-month periods before, during, and after biologic initiation for 12 weeks or more (i.e., consistent use). Results There were 63 instances of initiation of consistent biologic use (adalimumab [81%], infliximab [16%], and ustekinumab [3%]) in 57 patients. Patients' mean age was 40 years, 58% were female, and 53%/47% had Hurley stage II/III disease, respectively. Fewer patients required surgical/procedural interventions and systemic medications for the 6-month period during/6-month period after biologic initiation versus the 6-month period before biologic initiation, including intralesional corticosteroid injections (22%/14% vs 24%), incision and drainage (I&D) by physician (10%/10% vs 17%), I&D by patient (10%/10% vs 14%), surgical excision (8%/10% vs 11%), deroofing (5%/2% vs 5%), systemic antibiotics (43%/41% vs 54%), and systemic immunosuppressants (10%/6% vs 13%). Fewer patients required hospital admission for HS (17%/13% vs 21%) or emergency department visits for HS (8%/8% vs 16%) during the 6-month periods in which consistent biologics use started and continued versus the 6-month period before consistent biologic use. Conclusion Following initiation of consistent biologic use (12 weeks or more), fewer patients required acute procedural interventions, systemic medications, and healthcare utilization, supporting the importance of early biologic initiation.